Estudo de catalisadores bimetálicos Ni-Ag para a eletrooxidação de pequenas moléculas orgânicas visando à aplicação em fontes de energia sustentável - SANTOS, José Ribamar Nascimento dos (2022)
Ni−Ag nanoparticles supported on reduced graphene oxide (rGO) were investigated as electrocatalysts for the oxidation of ethanol, ethylene glycol, glycerol, and urea. The NiXAg100- X/rGO catalysts (X = 0, 50, 66, 75, 90 and 100) were prepared by the chemical reduction method, using sodium borohydride (NaBH4) as a reducing agent and characterized by the Fourier transform infrared spectroscopy technique (FTIR), UV-Vis spectroscopy, X-ray diffraction, scanning electron microscopy (SEM) and X-ray energy dispersive spectroscopy (EDS). The electrocatalytic activity of the materials in alkaline medium was evaluated by cyclic voltammetry (CV), chronoamperometry and electrochemical impedance spectroscopy (EIS). FTIR and UV-Vis spectra revealed that most of the functional groups containing oxygen were removed from graphene oxide by reduction with NaBH4. Composites of Ni−Ag alloys supported on rGO showed higher electrocatalytic activity compared to monometallic Ni(OH)2/rGO for ethanol, ethylene glycol and glycerol oxidation. In addition, the theoretical composition Ni66Ag34/rGO showed the best catalytic activity for the oxidation of these alcohols. Chronoamperometric curves recorded at 0.5 V confirm the superior stability of Ni−Ag/rGO catalysts during the oxidation of ethanol, ethylene glycol and glycerol. Regarding the oxidation of urea, the Ni90Ag10/rGO catalyst presented an onset potential of 0.291 V (vs. Ag/AgCl) and a current density of 109.3 mA cm-2 at 0.6 V, which shows a performance improved compared to Ni(OH)2/rGO (0.325 V and 78.2 mA cm-2 ). Ni90Ag10/rGO also exhibits good current retention during urea oxidation (98.6% for 3600 s). The good performance of Ni−Ag/rGO catalysts is attributed to the effect of the rGO support, as well as the synergistic effect between Ni and Ag.